NSCA's guide to tests and assessments - Miller, Todd (Science of strength and conditioning series., 2012)
This book offers strength and conditioning professionals a one-stop resource for the research-supported fitness and performance measures available. Created by top experts in the National Strength and Conditioning Association (NSCA), this comprehensive text offers extensive information on which factors matter and how to evaluate them as accurately and easily as possible. Editor Todd Miller and an authoritative team of contributors have compiled an exceptional reference and valuable tool for practicing professionals and an indispensable educational Todd Miller also includes NSCA-approved testing protocols, extensive references to current research, and applications for the testing of conditioning components. Information is presented in an accessible manner to help explain the findings of both researchers and practitioners so that readers can select the most effective and efficient approach for athlete and client assessments. This book is part of the Science of Strength and Conditioning series. Developed with the expertise of the National Strength and Conditioning Association (NSCA), this series of texts provides the guidelines for converting scientific research into practical application. The series covers topics such as tests and assessments, program design, and nutrition.